Haw pectin pentaglaracturonide inhibits fatty acid synthesis and improves insulin sensitivity in high-fat-fed mice. (July 2017) - Li, Suhong; Huang, Zhu; Dong, Yinping; Zhu, Rugang; Li, Tuoping
Highlights: HPPS inhibited fatty acid synthesis. HPPS attenuated high-fat-induced SREBF-1c activation. HPPS improved insulin sensitivity. Abstract: Haw pectin pentaglaracturonide (HPPS) significantly lowered the liver weights, hepatic triglycerides (TG) and total lipid levels of high-fat fed mice compared to those of high-fat control (HFC) mice, after 10 weeks administration. Similarly, high fat diets significantly increased plasma TG, non-esterified fatty acids, glucose, insulin and leptin levels compared to normal control diets, but were significantly decreased by HPPS supplementation after 10 weeks administration, these decreases however were not statistically significant at 4-week, compared to HFC diets. While, HPPS administration significantly increased adiponectin levels whatever at 4-week or 10-week. Further analysis found that HPPS administration significantly attenuated high-fat-induced SREBF-1c activation, decreased the levels of mRNA and protein, and enzyme activities of fatty acid synthase, acetyl-CoA carboxylase, and pyruvate kinase in the livers of mice compared to the high-fat control group. Moreover, prolonged administration of HPPS appeared to be more effective to achieve the above changes.